Genetic and climatic approaches reveal effects of Pleistocene refugia and climatic stability in an old giant of the Neotropical Dry Forest - Camps, Gonzalo Andres; Martinez Meyer, Enrique; Verga, Anibal; Sérsic, Alicia; Cosacov, Andrea (Oxford University Press, 2025)
Neotropical Dry Forests are important biodiversity hotspots characterized by intermediate to high levels of species richness and endemism. A possible explanation for these characteristics is that such forests have been less affected by drastic glacial impacts than other biomes. Using two approaches, geo-statistical phylogeography, based on two chloroplast markers, and multi-algorithm-based niche modelling, for the present and for the past, we explored if, during glacial periods, the geographical range of Bulnesia sarmientoi was stable or underwent expansions or retractions in space and time and if there is a relationship among past climatic refugia, the current climatic optimum and genetic diversity. We estimated that B. sarmientoi would have diverged from other Bulnesia at the beginning of the Pliocene (5 Mya), with diversification of the current lineages occurring in the Pleistocene (1.4–1.1 Mya). Our results suggest that Dry Forests underwent population expansion events during the glacial periods, whereas they would have undergone population stasis during interglacial periods. Furthermore, we identified a putative refugial area in the Dry Chaco that has been climatically stable through time, consistent with the area of highest genetic diversity and with the spatial location of the climatic optimum of the focal species.